Dynamic Control Balancing Cell Proliferation and Inflammation is Crucial for an Effective Immune Response to Malaria - Gupta, Anuj; Galinski, Mary R.; Voit, Eberhard O. (Frontiers in Molecular Biosciences, 2022)
Malaria has a complex pathology with varying manifestations and symptoms, effects on host tissues, and different degrees of severity and ultimate outcome, depending on the causative Plasmodium pathogen and host species. Previously, we compared the peripheral blood transcriptomes of two macaque species (Macaca mulatta and Macaca fascicularis) in response to acute primary infection by Plasmodium knowlesi. Although these two species are very closely related, the infection in M. mulatta is fatal, unless aggressively treated, whereas M. fascicularis develops a chronic, but tolerable infection in the blood. As a reason for this stark difference, our analysis suggests delayed pathogen detection in M. mulatta followed by extended inflammation that eventually overwhelms this monkey’s immune response. By contrast, M. fascicularis detects the pathogen earlier and controls the inflammation. Additionally, M. fascicularis limits cell proliferation pathways until the peak of an infection, presumably in an attempt to reinforce recovery. Here, we focus on molecular mechanisms underlying the key differences in the host and parasite responses and their coordination. Correlation analysis between host and pathogen transcripts reveals a similar but not identical pattern-recognition receptor signaling mechanism in the two hosts. Furthermore, during the initial parasitemic log phase of the infection, both hosts experience elevated inflammation, but ultimately address it differently. An important biomarker for inflammation is an altered kynurenine-tryptophan ratio, which leads to changes in NAD-mediated cell proliferation and immune activity via aryl hydrocarbon receptor (AhR) signaling. Downstream analysis of AhR signaling points to immune related genes like IL6 and IFN, as well as FOS genes that are involved in cell proliferation. In addition to controlling cell proliferation through Trp metabolism, M. fascicularis regulates cell proliferation through various mechanisms up to the time of peak parasitemia. A complete understanding of the exact dynamics of the immune response is difficult to reach. Nonetheless, our comparative analysis provides clear suggestions of processes that underlie an effective immune response. Thus, our study identifies multiple points of intervention that are apparently responsible for a balanced and effective immune response and thereby paves the way toward future immune strategies for treating malaria.